Wind/pinball ebook Two novels. - Murakami, Haruki (2015)
NATIONAL BESTSELLER Wind/Pinball, a unique two-in-one volume, includes, on one side, Murakami’s first novel  Hear the Wind Sing . When you flip the book over, you can read his second novel,  Pinball, 1973 . Each book has its own stunning cover. In the spring of 1978, a young Haruki Murakami sat down at his kitchen table and began to write. The result: two remarkable short novels— Hear the Wind Sing  and  Pinball, 1973 —that launched the career of one of the most acclaimed authors of our time. These powerful, at times surreal, works about two young men coming of age—the unnamed narrator and his friend the Rat—are stories of loneliness, obsession, and eroticism. They bear all the hallmarks of Murakami’s later books, and form the first two-thirds, with  A Wild Sheep Chase , of the trilogy of the Rat.  Widely available in English for the first time ever, newly translated, and featuring a new introduction by Murakami himself,  Wind/Pinball  gives us a fascinating insight into a great writer’s beginnings.